2015
DOI: 10.1080/01932691.2014.1003221
|View full text |Cite
|
Sign up to set email alerts
|

Dense Packed Layer Modeling in Oil-Water Dispersions: Model Description, Experimental Verification, and Code Demonstration

Abstract: In the present research paper modelling principles for the oil-water separation with special emphasis on the modelling of dense packed layer (DPL) is presented. Formation of the DPL is attributed to the difference between sedimentation rate and interfacial coalescence rate. Different sub-models resolving for the free sedimentation zone, the DPL, the binary coalescence and the interfacial coalescence are described. These submodels are implemented in commercial CFD software. Adequate validation and calibration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…According to the measured water content, the highest water content in the W/O emulsion phase appears to be at the emulsion interface. Such a phenomenon indicates that, instead of merging into the W/O emulsion phase, the dispersed oil droplets form a dense packed zone below the emulsion interface due to the difference between sedimentation rate and interfacial coalescence rate . The accumulation of oil droplets in the dense packed zone induced by the density difference changes the WOR and then leads to a catastrophic phase inversion. , Both high viscosity and the surface-active components make the sedimentation of water droplets in the newly formed W/O emulsion very slow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the measured water content, the highest water content in the W/O emulsion phase appears to be at the emulsion interface. Such a phenomenon indicates that, instead of merging into the W/O emulsion phase, the dispersed oil droplets form a dense packed zone below the emulsion interface due to the difference between sedimentation rate and interfacial coalescence rate . The accumulation of oil droplets in the dense packed zone induced by the density difference changes the WOR and then leads to a catastrophic phase inversion. , Both high viscosity and the surface-active components make the sedimentation of water droplets in the newly formed W/O emulsion very slow.…”
Section: Resultsmentioning
confidence: 99%
“…The bottle test, because of its operational simplicity, is generally conducted to evaluate the stability of different dispersion systems and monitor the demulsification process by measuring the volume of separated phases. Hartland and Jeelani developed a series of empirical formulas to predict the heights of the dense packed zone and the sedimentation zone at which the emulsion phase is located after dividing a demulsifying liquid–liquid dispersion system at atmospheric conditions into four parts: (1) a lighter pure phase, (2) a sedimentation zone, (3) a dense packed zone, and (4) a heavier pure phase. By measuring water cut at the oil and water outlets of a horizontal separator, Panjwani et al simulated the coalescence behavior in an inversed dense packed zone by using computational fluid dynamics (CFD). Sheng found that during chemical flooding the type of emulsion also depends on the water–oil ratio (WOR).…”
Section: Introductionmentioning
confidence: 99%